Good governance as key to the flow of foreign development aid: the sub-Saharan Africa perspective - Gezimati, Robinson (Research of GSB, 2019)
The aim of this study was to evaluate the importance of good governance to the flow of foreign development aid. The researcher used the sub-Saharan Africa region to accomplish the aim of his study. The study examined the extent to which foreign development aid has been targeted at countries with sound governance systems, that is, strong institutions and policies. This study therefore determined whether the flow of foreign development aid in sub-Saharan African developing countries has changed since the endorsement of the “Monterrey Consensus” by targeting those countries with sound economic institutions and policy environments. Empirical and theoretical literature was reviewed on foreign development aid as well as governance systems especially the Ibrahim Index of African Governance (IIAG), which was discussed and used in this study as the governance indicator system. The study’s results and findings were deduced from secondary data which addressed the governance indicators in sub-Saharan Africa for 2010 to 2015, gathered from the IIAG assessment reports of 12 selected sub-Saharan African countries as well as the amount of foreign development aid received by each of the countries during the same period gathered from OECD and World Bank statistics. Additionally, inferential analysis was undertaken using the Spearman’s correlation test as well as a multiple linear regression analysis to establish the relationships and/or impact of the governance indicators on the flow of foreign development aid to sub-Saharan Africa. The study concluded that the combined effect of all the governance indicators have a statistical significant effect on the flow of foreign development aid to developing countries in sub-Saharan Africa. Individually, Participation and Human Rights indicators as well as Sustainable Economic Opportunities indicators have a positive effect or impact on the flow of foreign development aid in sub-Saharan African countries, with Sustainable Economic Opportunities indicators having the highest impact. However, Safety and Rule of Law indicators were discovered to have a negative effect on the flow of foreign development aid in sub-Saharan Africa whilst Human Development indicators were discovered not to have any effect or impact. On the other hand, the study also noted that in further determining allocations funding agencies may consider a country’s Safety and Rule of Law indicators as well as Human Development indicators whilst Participation and Human Rights indicators and Sustainable Economic Opportunity indicators were seen not have any significant effect on determination of funding allocations.